2020
DOI: 10.3389/fmicb.2020.593542
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Antibiotic Resistance in Surrogates of Francisella tularensis (LVS and Francisella novicida): Effects on Biofilm Formation and Fitness

Abstract: Francisella tularensis, the causative agent of tularemia, is capable of causing disease in a multitude of mammals and remains a formidable human pathogen due to a high morbidity, low infectious dose, lack of a FDA approved vaccine, and ease of aerosolization. For these reasons, there is concern over the use of F. tularensis as a biological weapon, and, therefore, it has been classified as a Tier 1 select agent. Fluoroquinolones and aminoglycosides often serve as the first line of defense for treatment of tular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 96 publications
3
31
0
Order By: Relevance
“…Francisella has been shown to form biofilms ( Dean et al, 2009 ; Durham-Colleran et al, 2010 ; Margolis et al, 2010 ; Chung et al, 2014 ; Champion et al, 2019 ). Francisella embedded in these biofilms were shown to have increase AMR compared to planktonic cells ( Biot et al, 2020 ; Siebert et al, 2020 ), similar to what has been observed with other bacteria ( Singh et al, 2017 ). This is thought to be mainly due to poor diffusion of the antibiotics through the extracellular polysaccharide matrix that makes up the biofilm.…”
Section: Phenotypic Resistancesupporting
confidence: 78%
See 3 more Smart Citations
“…Francisella has been shown to form biofilms ( Dean et al, 2009 ; Durham-Colleran et al, 2010 ; Margolis et al, 2010 ; Chung et al, 2014 ; Champion et al, 2019 ). Francisella embedded in these biofilms were shown to have increase AMR compared to planktonic cells ( Biot et al, 2020 ; Siebert et al, 2020 ), similar to what has been observed with other bacteria ( Singh et al, 2017 ). This is thought to be mainly due to poor diffusion of the antibiotics through the extracellular polysaccharide matrix that makes up the biofilm.…”
Section: Phenotypic Resistancesupporting
confidence: 78%
“…Generally, doxycycline is very effective against tularemia with an MIC reported between 0.064 and 4 mg/L and no doxycycline-resistant strains have been reported in nature ( Caspar and Maurin, 2017 ). Interestingly, ciprofloxacin-resistant Francisella strains have an approximately 2–10-fold increase in the MIC for doxycycline in two studies, suggesting that some cross-resistance may be happening ( Biot et al, 2020 ; Sutera et al, 2014b ). There is overall very little research on the mechanism and frequency of doxycycline resistance in Francisella .…”
Section: Intrinsic Antibiotic Resistance In Francisellamentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, as F. tularensis is a facultative intracellular bacterium, any offered antibiotic should have intracellular pharmacokinetic and pharmacodynamic activity [ 30 , 31 ]. To note, resistant strains can be easily selected in vitro [ 32 , 33 , 34 , 35 , 36 ], thus ASTs should be applied prior to treatment selection, especially following a bioterror event.…”
Section: Bacterial Bioterror Agents— B Anthracis Y Pestis and F Tularensismentioning
confidence: 99%